Identifying Proprietary Channel Impact as A Digital Financial Services Indicator on Inflation in Indonesia - Rahayu, Rahayu; Luthfi, Musthafa; Albetris, Albetris; Rahman, Failur; Nurhayani, Nurhayani (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
Availability of financial services by Banks in Indonesia can make transactions in some sectors of economy more flexible and easier. This inclusiveness creates a new habit in society for payments, money transfer, and other transaction, furthermore, the use of digital financial services can boost the selling performance of MSME’s, especially in e-commerce. Nowadays, the increasing of digital financial services using, affecting money in circulation to prevent inflation. This research aims to measure the extent of the digital financial services can impact inflation by measuring of money supply that use a digital financial service making an econometrics model of Error Correction Model. This model construct of digital financial services that be indicated by proprietary channel. Some variable of proprietary channel includes the use of mobile-internet banking as first variable and the use of phone banking as second variable. This research will find which variable can affect the money supply as an inflation indicator. The finding of this research can be concluded that mobile-internet banking has a significant impact on inflation and phone banking has a significant impact on inflation too. These variables also have simultaneously significant impact on inflation in short run and in long run. So, maintaining inflation have to be considered by the relevant authority.